2019
DOI: 10.1371/journal.pone.0220907
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of miRNAs and mRNAs reveals the potential regulatory role of miRNAs in the developmental process of early weaned goats

Abstract: MicroRNAs (miRNAs) play pivotal roles in growth, development, and stress responses. However, the regulatory function of miRNAs in early weaned goats remains unclear. Deep sequencing comparison of mRNA and miRNA expression profiles showed that 18 miRNAs and 373 genes were differentially expressed in pre- and post-weaning Chongming white goats. Bioinformatics analysis indicated that these differentially expressed genes are involved in cellular processes, developmental processes, and growth in terms of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In goat kids, blood miRNA and mRNA signatures were investigated 1 day before weaning (44 days of age) and 3 days after weaning (48 days of age). Eighteen miRNAs (8 upregulated and 10 downregulated) and 373 genes were found to be DE (111). Two miRNAs related to skeletal muscle development (miR-206 and miR-133a/b) were significantly downregulated in post-weaning animals, as were cell proliferation-associated miRNAs (miR-99b-3p, miR-224, miR-143-5p, and miR-10b-5p).…”
Section: Animal Management-related Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In goat kids, blood miRNA and mRNA signatures were investigated 1 day before weaning (44 days of age) and 3 days after weaning (48 days of age). Eighteen miRNAs (8 upregulated and 10 downregulated) and 373 genes were found to be DE (111). Two miRNAs related to skeletal muscle development (miR-206 and miR-133a/b) were significantly downregulated in post-weaning animals, as were cell proliferation-associated miRNAs (miR-99b-3p, miR-224, miR-143-5p, and miR-10b-5p).…”
Section: Animal Management-related Stressmentioning
confidence: 99%
“…Two miRNAs related to skeletal muscle development (miR-206 and miR-133a/b) were significantly downregulated in post-weaning animals, as were cell proliferation-associated miRNAs (miR-99b-3p, miR-224, miR-143-5p, and miR-10b-5p). This suggested that weaning stress induced growth retardation in the animals through the repression of cell proliferation, and the authors proposed that significantly altered levels of these miRNAs may be potential biomarkers to assess the severity of weaning stress in goat production (111).…”
Section: Animal Management-related Stressmentioning
confidence: 99%
“…It should be stressed that, although the diseases have different aetiologies, CAE is considered the animal model of this disorder 23 . Moreover, miR-214 , which plays contradictory roles in SARS-CoV infection in humans, also downregulates the expression of the lactoferrin gene in human mammary epithelial cells 24 . Elevated miR-141 expression has been observed during enterovirus infection of rhabdomyosarcoma cells 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Specific changes in urinary miRNA expression in male goats during the breeding season may be related to their high testosterone levels during breeding (Longpre et al, 2014 ). Serum miRNA expression profiles are different in Chongming white goats pre- and post-weaning (Liao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%